AMNESTI TERHADAP HASTO KRISTIYANTO: ANTARA REKONSILIASI POLITIK DAN TANTANGAN SUPREMASI HUKUM DI INDONESIA - Ramlin Ahmad; Heli Komarudin; Dhimas Dwi Putro Baharza; Azis Nur Arifin; Chaliza Yafirastiani Pangestu; Yossy Aulia Fadli (Universitas Kapuas, 2026)
This study examines the granting of amnesty to Hasto Kristiyanto by the President of the Republic of Indonesia from July to August 2025. This study assesses the legal basis of the amnesty, the political process that accompanied it, and its impact on the principle of the rule of law and the eradication of corruption in Indonesia. The method used is a qualitative research with a document study approach—using news from mainstream media, official government statements, statements from the Corruption Eradication Commission (KPK), and analysis from legal experts. The results of the study found that although amnesty is officially the prerogative of the president after obtaining approval from the House of Representatives, granting amnesty to political actors in corruption cases creates an ethical and normative dilemma: it can be seen as a tool for political reconciliation, but has the potential to harm a sense of substantive justice and trust in law enforcement. Recommendation: There is a need for restrictions on amnesty policies for corruption cases through strong transparency mechanisms and increased accountability forums in the political and legal spheres.